Migránsok, menekülők, szerencsét próbálók és társaik. I. rész - Dövényi, Zoltán (Közép-Európai Közlemények, 2016)
Undoubtedly, 2015 was the year of migration in Europe: much more than one million people arrived to the „old continent” from not european contries – most of them without registration and authority controll. The questions and problems emerged in this study refer to this massive migration: 1. Why 2015 was the very year, when migrants started to get going? We can specify more reasons (which are connected or build on each other) • Syrian war consists. •The Balkan migration corridor opened. • Turkey’s languidity in stop of migration. • Greek’s poor performance in reception of migrants adequately to EU regulations. • Germany’ inviting behaviour to syrian migrants. 2. Who arrived and what do they want? As registration of migrants are very defective, we hardly have reliable information about these people. Sure: • Men are overrepresented. • Young age groups (< 30 years) make the major part of migrants. • Yearly sure: • In the case of the most migrants educational achivement is low. • Fast labour market integration of them is very doubtful.